Isolation and characterization of antagonistic bacteria against Vibrio harveyi from milkfish Chanos chanos - Krishnani, Kishore K.; Kathiravan, V.; Kailasam, M.; Nagavel, A.; Ponniah, A. G. (Indian Journal of Fisheries, 2019)
Vibrio species are the most dominant multidrug-resistant opportunistic bacterial pathogens in coastal aquaculture environments. There is an urgent need for biocontrol strategy to enhance commercially viable shrimp production. In the present study, eight strains of Bacillus were isolated and characterised from surface mucus of milk fish maintained in greenwater system and their antagonistic effects were evaluated against shrimp pathogenic bacteria Vibrio harveyi, by agar well diffusion and co-culture methods. Promising organisms were immobilised onto a matrix for preparation of bioaugmentor and again tested for antagonistic activity against V. harveyi.